International Development Cooperation : Set of Lectures - Bartenev, Vladimir; Glazunova, Elena (World Bank, Moscow, 2013)
This set of lectures is structured in accordance with the aforementioned objectives. It is divided into four parts. Part one examines the theoretical-methodological issues of development studies that remain largely a terra incognita for the Russian audience. The authors deliberately differentiated between two terms, development and international development assistance . The most voluminous Part two examines the key issues pertaining to aid architecture. In the beginning the authors reconstruct the terminological and institutional-legal system in which international development assistance is provided currently, classify the main criteria, forms, and modalities of aid, as well as identify key international development actors. The first introductory lecture is followed by a description of the latest trends in composition and distribution of aid flows with breakdowns by donor group, aid modality, region, country, income group, and sector. There is an analysis of those trends which hinder progress in increasing aid effectiveness. The authors develop the idea that international development assistance is a form of cooperation in which both donors and recipients (regardless of the differences in their motivation, interests, goals, and strategies) are engaged as partners. However, it is still the donors that drive the agenda. That is why most of attention in part two is paid to donors, both established and emerging ones. An analysis is provided of commonalities and particularities of donor national strategies of participation in international development cooperation. Part three is entirely devoted to the practical aspects of providing assistance, management, financing, monitoring and evaluation of aid programs. This section explores a wide range of issues, such as specifics of aid management systems, planning expenditures for bilateral and multilateral aid programs, advantages and shortcomings of various aid modalities and channels of aid delivery, as well as the project-based and program-based approaches. The last part, part four, sheds light on the provision of development assistance in specific spheres, such as support for production growth (including aid for trade), infrastructure (transport, energy, information and communications technologies), social services (education, health, water supply, and sanitation), and environment.